Preparation and characterization of a novel magnetic nano adsorbent for removal of metal ions - Mutairah S. Alshammari; Marwa M. El-Tyieb; Mariam E. Fawzy; Eida S. Al-Farraj; Hussein M. Ahmed (PLoS ONE, 2025)
As a result of global urbanization and industrialization, heavy metals are one of the hazardous contaminants facing the world. The adsorption process using agricultural wastes can achieve one of the sustainable development goals for wastewater treatment and resource recovery. Moringa and tea extracts were utilized to synthesize iron nanoparticles for the treatment of aqueous solutions containing heavy metal ions (Cu2+, Pb2+, Se2+, Zn2+, and Cr6+). This method offers a sustainable substitute for conventional chemical wastewater treatment methods. Furthermore, the use of magnetic iron nanoparticles reduces the need for extra separation processes by making it simple to separate the adsorbent from the treated waste using a magnetic field. Various techniques were employed to characterize the prepared nanoparticles, such Fourier-transform infrared spectroscopy (FT-IR), energy dispersive x-ray spectroscopy (EDX), scanning electron microscopy (SEM), x-ray diffraction (XRD), and x-ray fluorescence (XRF). The XRD analysis confirmed the crystalline phase of alpha-FeNPs in the synthesized nanoparticles. The EDX analysis verified the presence of oxygen and iron in the nanoparticles, indicating that the iron was in an oxide form. This study aimed to investigate the removal of heavy metals using nano-magnetic composites of moringa (FeNPs-M) and tea (FeNPs-T). To assess the effectiveness of the FeNPs-M several parameters were tested, including pH, contact time, initial concentration, and nanoparticle dosage. The results indicated that the efficiency of FeNPs-M was significantly higher than that of FeNPs-T for the removal of heavy metals from synthetic solutions, achieving removal efficiency are 96.5% 99.71%, 96.73%, 93.16%, and 91.83% of Cu2+, Pb2+, Se2+, Zn2+, and Cr6+, respectively, when using FeNPs-M, while the removal efficiency are 96.36%, 93.40%, 79.83%, 78.6%, and 77.77% of Cu2+, Pb2+, Se2+, Zn2+, and Cr6+, respectively, 25 °C, with a contact time of 45 min, a pH of 3.0, concentration 3.0 mg/L, a sorbent dose of 0.8 g/L, and 200 rpm at 25 °C.